PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP REAKSI PASAR - Christina Widhi Astuti; Yeterina Widi Nugrahanti (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
The objective of this research is to examine the effect of Corporate Social Responsibility (CSR) disclosure toward market reaction. CSR disclosure is measured by comparing the corporation CSR disclosure with the GRI standart. Market reaction is measured by abnormal return and unexpected trading volume. The sample of this research consist of 118 manufacture companies listed on the Indonesia Stock Exchange (BEI) in 2013. Multiple regressions were used to analyze the data. Based on the research, the result showed that the CSR Dislosures have no effect toward abnormal return and unexpected trading volume. Keywords : corporate social responsibility (CSR) disclosure, abnormal return, unexpected trading volume